Method for promoting mass precipitation and uniform distribution of Mn-rich phase in Al-Mg-Mn alloy
By adding Si and Cr to the Al-Mg-Mn alloy and performing three-stage homogenization heat treatment, the problem of uneven distribution of Mn-rich phases is solved, and its uniform precipitation in dendrites is achieved, which significantly improves the mechanical and corrosion performance of the alloy.
Patent Information
- Application Number
- CN202411907838.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-23
- Publication Date
- 2025-04-25
AI Technical Summary
In existing Al-Mg-Mn alloys, Mn elements tend to gather near the grain boundaries and dendrites during solidification, resulting in uneven distribution of Mn-rich phases, affecting the recrystallization resistance, mechanical properties and corrosion properties of the alloy.
By adding Si to the Al-Mg-Mn alloy or adding Si and Cr in composite, and performing a three-stage homogenization heat treatment, the Mn-rich phase precipitation in dendrites is promoted in large and uniform manner.
The state of rapid, large and dispersed Mn-rich phase in dendrites is achieved, eliminating the obvious DFZ area in dendrites' arm spacing and quantitative analysis results, and significantly improving the mechanical properties and corrosion properties of the alloy.
Smart Images

Figure BDA0005204829810000071 
Figure HDA0005204829960000011 
Figure HDA0005204829960000012
Abstract
Description
Technical field:
[0001] The present invention belongs to the technical field of metal alloys, and specifically relates to a method for promoting the precipitation and uniform distribution of a large amount of Mn-rich phase in an Al-Mg-Mn alloy, which is mainly achieved by regulating the alloy composition and heat treatment process. The large amount of precipitation and uniform distribution of the second phase makes the aluminum alloy have excellent comprehensive properties, and can effectively improve the recrystallization resistance, mechanical properties and corrosion properties of the alloy in the subsequent deformation process. Background technology:
[0002] Al-Mg alloys are widely used in the fields of construction, transportation, and marine engineering due to their low density, high specific strength, good corrosion resistance, and excellent weldability. Mn is the most common microalloying element in Al-Mg alloys. The addition amount is usually controlled below 1.0wt.%, and it usually exists in the form of solid solution and Al6Mn precipitation phase. Mn in solid solution can improve the strength of the alloy through solid solution strengthening. Every increase of 1wt.% of Mn can increase the strength by about twice that of adding the same mass percentage of Mg element. The Al6Mn phase precipitated during the heat treatment process can slightly increase the strength and recrystallization temperature of the alloy. In addition, Al6Mn acts as a nucleation site for the precipitation of β phase, and β phase can precipitate at the interface between Al6Mn phase and matrix, thereby reducing the enrichment of β phase at the grain boundary, thereby improving the corrosion resistance of the alloy.
[0003] The beneficial effect of adding Mn elements to Al-Mg alloys is obvious. However, due to the solute redistribution of Mn elements during the solidification process, in the cast alloy, Mn elements tend to be concentrated near the grain boundaries and dendrite boundaries. However, during the subsequent homogenization heat treatment process, the Al6Mn phase tends to precipitate near the grain boundaries and dendrite boundaries, while a Mn-rich depleted zone is formed in the center of the dendrite. This uneven distribution of the precipitation characteristics of the second phase can easily lead to a weakening of the alloy's recrystallization resistance during the subsequent rolling process, which will have an adverse effect on the mechanical properties and corrosion properties of the alloy plate.
[0004] Si is generally considered to be a common impurity element in aluminum alloys, and its influence on the precipitation of various strengthening phases in aluminum alloys has received widespread attention. The literature points out that after adding Si elements, the β' (Mg-Si) phase formed during the heat treatment process can serve as a heterogeneous nucleation site for the Mn-rich phase, greatly promoting the precipitation of the Mn-rich phase. However, it can be seen from the Al-Si eutectic phase diagram that Si elements tend to segregate to the dendrite edge and the area near the grain boundary during solidification, so the β' phase precipitated during the subsequent heat treatment process still shows a state of gradually decreasing from the grain boundary, dendrite boundary to the center, so it is still difficult to solve the problem of relying solely on the β' phase to provide heterogeneous nucleation sites to precipitate the Al6Mn phase in the center of the dendrite. Moreover, in high-Mg aluminum alloys, because Si atoms have a strong affinity with Mg atoms, the amount of Si element added needs to be strictly controlled to prevent the formation of a large number of large-sized primary Mg2Si phases in the cast structure. In the homogenization heat treatment process commonly used in 5xxx series aluminum alloys, this primary phase with a higher melting point is difficult to dissolve back into the Al matrix, which can easily have an adverse effect on the hot working properties of the alloy. Therefore, the addition amount of Si element in high Mg aluminum alloys needs further study.
[0005] It is worth noting that from the Al-Cr phase diagram, it can be seen that Cr and Al undergo a peritectic reaction, and the Cr element is easily enriched in the center of the dendrite during solidification. The literature points out that Cr can promote the precipitation of Al-Mn phase in the center of the dendrite, and Cr atoms can replace some Mn atoms in the Al-Mn phase to form Al-Mn-Cr phase. Because the diffusion rate of the Cr element is 2-3 orders of magnitude lower than that of the Mn element, the thermal stability of the formed Al-Mn-Cr phase is further increased. At the same time, the addition of Cr element should not be too much, otherwise it is easy to produce coarse primary Al-Cr phase, which is easy to cause brittle fracture during the tensile process, and has an adverse effect on the mechanical properties of the alloy.
[0006] The present invention is based on the above considerations, adding Si or Si and Cr in combination to the Al-Mg-Mn alloy, and performing appropriate homogenization heat treatment to promote the precipitation of the second phase (the second phase in the present invention refers to the Mn-rich phase), so that it is evenly distributed in the dendrites, thereby improving the comprehensive properties of the Al-Mg-Mn alloy. Summary of the invention:
[0007] The object of the present invention is to provide a method for promoting the precipitation of a large amount of Mn-rich phase and its uniform distribution in an Al-Mg-Mn alloy, and specifically to provide an alloy composition and a heat treatment process for promoting the precipitation of a large amount of Mn-rich phase and its uniform distribution in an Al-Mg-Mn alloy. By means of a composite microalloying method, the synergistic effect of the eutectic element Si and the peritectic element Cr is brought into play, and the optimal composition range and heat treatment process are explored to promote the precipitation of a large amount of the second phase in the Al-Mg-Mn alloy and make it uniformly distributed, thereby improving the comprehensive performance of the Al-Mg-Mn alloy.
[0008] The present invention provides an alloy composition and a heat treatment process for promoting the precipitation and uniform distribution of a large amount of Mn-rich phase in an Al-Mg-Mn alloy, which specifically comprises the following steps:
[0009] Step 1: A conventional metal mold casting method is used to obtain an aluminum alloy ingot, wherein the mass percentages of the constituent elements of the alloy are: Mg: 4.0-6.0wt.%, Mn: 0.4-1.0wt.%, Si: 0-0.4wt.% and not 0 (preferably 0.1-0.2wt.%), Cr: 0-0.4wt.% and not 0 (preferably 0.1-0.2wt.%), and the rest are Al and some unavoidable impurities.
[0010] Step 2: Cut off the head and tail of the ingot obtained in step 1, and take a sample from the center of the ingot for homogenization heat treatment. The homogenization heat treatment process is a three-stage homogenization process, wherein the first stage heat treatment temperature is the precipitation temperature of the β' phase (usually 250°C-300°C), and the holding time is 8-12h (preferably 280°C, holding time 12h).
[0011] The main purpose of this step is to allow the β' phase to fully precipitate during the slow heating process, providing favorable heterogeneous nucleation sites for the precipitation of the Al-Mn phase during the subsequent heat treatment process.
[0012] The sample after the first stage heat treatment is further heated up for the second stage heat treatment, wherein the second stage heat treatment temperature is the precipitation temperature of the Al-Mn phase (usually 350°C-400°C), and the insulation time is 12-60h (preferably 375°C for 48h).
[0013] The main purpose of this step is to fully precipitate the Al-Mn phase during the second stage heat treatment, reduce the supersaturation of the Mn element in the Al matrix, and thus reduce the coarsening of the Al-Mn phase during the subsequent high temperature heat treatment. In addition, most of the β' phase precipitated during the first stage heat treatment will gradually dissolve back into the Al matrix during the second stage heat treatment.
[0014] The sample after the second stage heat treatment is further heated for the third stage heat treatment, wherein the third stage heat treatment temperature is the dissolution temperature of the primary β(Al3Mg2) phase in the Al-Mg alloy (usually 420°C-500°C), and the insulation time is 8-24h (preferably 450°C for 12h).
[0015] The first, second and third stages in the above heat treatment process all control the heating rate to be no less than 0.5°C / min, but no more than 1.5°C / min, and the heating rates of the three stages are the same, in order to allow the alloy elements to diffuse fully.
[0016] The main purpose of this step is: 1. To make the main alloy element Mg diffuse gradually and evenly to eliminate element segregation; 2. To make the primary β (Al3Mg2) phase in the cast structure gradually dissolve back into the Al matrix to facilitate subsequent hot deformation processing. 3. To make the Al-Mn-Cr phase precipitate in the center of the dendrite at a higher temperature.
[0017] Step 3: Air-cool the sample after the three-stage homogenization heat treatment to room temperature for performance testing and microstructure observation.
[0018] The present invention has the following beneficial effects:
[0019] The present invention adds Si or Si and Cr elements to the Al-Mg-Mn alloy, performs a three-stage homogenization heat treatment while ensuring that the content of the insoluble primary phase (mainly referring to the Al-Mn phase and the Mg-Si phase) is low, so that the second phase can be rapidly, massively and dispersedly precipitated in the entire dendrite. Among them, the precipitated phase near the edge of the dendrite is the Al-Mn phase, and the precipitated phase at the center of the dendrite is the Al-Mn-Cr phase. Compared with the more dispersed phase-free precipitation zones (DFZ) existing in the traditional Al-Mg-Mn alloy after the traditional homogenization heat treatment, the alloy of the specific composition involved in the present invention has no obvious DFZ area in the microstructure after the three-stage homogenization heat treatment, which effectively improves the mechanical properties of the alloy. Description of the drawings:
[0020] Figure 1 : Microstructure of 0.1Si modified alloy during two-stage heat treatment: (a) 280℃ / 12h+375℃ / 12h; (b) 280℃ / 12h+375℃ / 24h; (c) 280℃ / 12h+375℃ / 48h.
[0021] Figure 2 : Microstructures of alloys with different compositions after three-stage homogenization heat treatment: (a) Base alloy (Example 4); (b) 0.1Si (Example 5); (c) 0.2Si (Example 6); (d) 0.2Si+0.2Cr (Example 7).
[0022] Figure 3 : Properties of alloys with different compositions after three-stage homogenization heat treatment: (a) hardness value (HV); (b) difference in electrical conductivity between the three-stage homogenization heat treated state and the cast state. Specific implementation method:
[0023] The present invention will be further described below in conjunction with examples, but the present invention is not limited to the following examples.
[0024] Example 1
[0025] The aluminum alloy ingot of this embodiment is obtained by the traditional metal mold casting method. The mass percentages of the constituent elements of the alloy are: Mg: 4.0wt.%, Mn: 0.8wt.%, Si: 0.1wt.%, Cr: 0.0wt.%, and the rest are Al and some inevitable impurities. The ingot is cut off from the head and tail, and a sample from the center of the ingot is taken for homogenization heat treatment (Note: the heating rate is 1°C / min). Among them, the first stage heat treatment temperature is 280°C, and the holding time is 12h; the second stage heat treatment temperature is 375°C, and the holding time is 12h. This heat treatment state is defined as DH12 (280°C / 12h+375°C / 12h). The sample after DH12 heat treatment is subjected to scanning microstructure observation, as shown Figure 1 Middle a.
[0026] Example 2
[0027] The aluminum alloy ingot of this embodiment is obtained by the traditional metal mold casting method. The mass percentages of the constituent elements of the alloy are: Mg: 4.0wt.%, Mn: 0.8wt.%, Si: 0.1wt.%, Cr: 0.0wt.%, and the rest are Al and some inevitable impurities. The ingot is cut off from the head and tail, and a sample from the center of the ingot is taken for homogenization heat treatment (Note: the heating rate is 1°C / min). Among them, the first stage heat treatment temperature is 280°C, and the holding time is 12h; the second stage heat treatment temperature is 375°C, and the holding time is 24h. This heat treatment state is defined as DH24 (280°C / 12h+375°C / 24h). The sample after DH24 heat treatment is subjected to scanning microstructure observation, as shown in the figure. Figure 1 Middle b.
[0028] Example 3
[0029] The aluminum alloy ingot of this embodiment is obtained by the traditional metal mold casting method. The mass percentages of the constituent elements of the alloy are: Mg: 4.0wt.%, Mn: 0.8wt.%, Si: 0.1wt.%, Cr: 0.0wt.%, and the rest are Al and some inevitable impurities. The ingot is cut off from the head and tail, and a sample from the center of the ingot is taken for homogenization heat treatment (Note: the heating rate is 1°C / min). Among them, the first stage heat treatment temperature is 280°C, and the holding time is 12h; the second stage heat treatment temperature is 375°C, and the holding time is 48h. This heat treatment state is defined as DH48 (280°C / 12h+375°C / 48h). The sample after DH48 heat treatment is subjected to scanning microstructure observation, as shown in the figure. Figure 1 Middle c.
[0030] Examples 1-3 are mainly for the regulation of the second stage heat treatment process, which is the most important of the three-stage heat treatment process. The difference between Examples 2 and 3 and Example 1 is the difference in the second stage heat treatment time. As the second stage heat treatment time increases, the second phase gradually precipitates slowly, the area proportion of the DFZ region gradually decreases, and the dendrite arm spacing also gradually decreases. The quantitative analysis results are shown in Table 1. Combining the precipitation state of the second phase and the heat treatment process, Example 3 reaches the best precipitation state after DH48 heat treatment.
[0031] Table 1
[0032]
[0033] Example 4
[0034] The aluminum alloy ingot of this embodiment is obtained by a traditional metal mold casting method, and the mass percentages of the constituent elements of the alloy are: Mg: 4.0wt.%, Mn: 0.8wt.%, Si: 0.0wt.%, Cr: 0.0wt.%, and the rest are Al and some inevitable impurities. The ingot is cut off from the head and tail, and a sample from the center of the ingot is taken for homogenization heat treatment (Note: the heating rate is 1°C / min). Among them, the first stage heat treatment temperature is 280°C, and the holding time is 12h; the second stage heat treatment temperature is 375°C, and the holding time is 48h; the third stage heat treatment temperature is 450°C, and the holding time is 12h. The metallographic structure of the sample after the three-stage homogenization heat treatment is observed, as shown Figure 2 Middle a.
[0035] Example 5
[0036] The aluminum alloy ingot of this embodiment is obtained by a traditional metal mold casting method, and the mass percentages of the constituent elements of the alloy are: Mg: 4.0wt.%, Mn: 0.4wt.%, Si: 0.1wt.%, Cr: 0.0wt.%, and the rest are Al and some inevitable impurities. The ingot is cut off from the head and tail, and a sample from the center of the ingot is taken for homogenization heat treatment (Note: the heating rate is 1°C / min). Among them, the first stage heat treatment temperature is 280°C, and the holding time is 12h; the second stage heat treatment temperature is 375°C, and the holding time is 48h; the third stage heat treatment temperature is 450°C, and the holding time is 12h. The metallographic structure of the sample after the three-stage homogenization heat treatment is observed, as shown Figure 2 Middle b.
[0037] Example 6
[0038] The aluminum alloy ingot of this embodiment is obtained by a traditional metal mold casting method, and the mass percentages of the constituent elements of the alloy are: Mg: 4.0wt.%, Mn: 0.8wt.%, Si: 0.2wt.%, Cr: 0.0wt.%, and the rest are Al and some inevitable impurities. The ingot is cut off from the head and tail, and a sample from the center of the ingot is taken for homogenization heat treatment (Note: the heating rate is 1°C / min). Among them, the first stage heat treatment temperature is 280°C, and the holding time is 12h; the second stage heat treatment temperature is 375°C, and the holding time is 48h; the third stage heat treatment temperature is 450°C, and the holding time is 12h. The metallographic structure of the sample after the three-stage homogenization heat treatment is observed. Figure 2 Middle c.
[0039] Example 7
[0040] The aluminum alloy ingot of this embodiment is obtained by a traditional metal mold casting method, and the mass percentages of the constituent elements of the alloy are: Mg: 4.0wt.%, Mn: 0.8wt.%, Si: 0.2wt.%, Cr: 0.2wt.%, and the rest are Al and some inevitable impurities. The ingot is cut off from the head and tail, and a sample from the center of the ingot is taken for homogenization heat treatment (Note: the heating rate is 1°C / min). Among them, the first stage heat treatment temperature is 280°C, and the holding time is 12h; the second stage heat treatment temperature is 375°C, and the holding time is 48h; the third stage heat treatment temperature is 450°C, and the holding time is 12h. The metallographic structure of the sample after the three-stage homogenization heat treatment is observed. Figure 2 Middle d.
[0041] Examples 4-7 are mainly aimed at regulating the influence of alloy composition on the precipitation of the second phase after the three-stage homogenization heat treatment. The difference between Examples 5-7 and Example 4 is that the alloy composition is different. Compared with Example 4 without Si, the area proportion of the DFZ region in Examples 5 and 6 after the three-stage homogenization heat treatment is greatly reduced, but there is still a small amount of DFZ in the center of the dendrite. This is because under the cast condition, the constituent elements Mg and Si of the β' phase are segregated to the edge of the dendrite, and the nucleation of the β' phase will be more likely to occur in these areas with high supersaturation, and much slower or not at all in the center of the dendrite, so the Al-Mn phase cannot make up for the state of no precipitation in the center of the dendrite even through heterogeneous nucleation precipitation. Moreover, the diffusion rate of the Mn element is low at less than 400°C, and it cannot diffuse over a long distance to the center of the dendrite for large-scale precipitation. Compared with Example 6, the addition of trace Cr (peritectic element) in Example 7 causes a large amount of Al-Mn-Cr phase to precipitate in the center of the dendrite, and there is no obvious DFZ in the entire organization. Therefore, after the addition of trace amounts of Si and Cr and the three-stage homogenization heat treatment, the second phase reaches a dispersed distribution state in the alloy. Figure 3 In a, it is the hardness curve of the alloys of the four components after the three-stage homogenization heat treatment. It can be seen that compared with the basic alloy in Example 4, the hardness value of the modified alloy gradually increases and reaches the maximum in Example 7. Figure 3 Figure b is the conductivity difference curve of the alloy of the four components in the three-stage homogenization heat treatment state and the cast state. The trace amount of Si in Example 5 can greatly promote the precipitation of the second phase, and the conductivity difference reaches the maximum in Example 7 where Si and Cr are added at the same time. Figure 2 Microstructural evolution and Figure 3 According to the hardness and conductivity change trends in the alloy, Si and Cr are preferably added synergistically as the optimal alloy components.
[0042] The difference between Example 1-3 and Example 4-7 is that the former mainly regulates the second-stage heat treatment process, while the latter mainly regulates the alloy composition. The optimization of the alloy composition combined with the optimization of the second-stage heat treatment process is the main innovation of the present invention. Ultimately, by regulating the precipitation of the second phase, there is basically no obvious DFZ area in the organization. Literature data show that in the subsequent heat treatment process, recrystallization is more likely to initiate in the DFZ area. The DFZ zone in the center of the dendrite easily makes the corrosion rate of the alloy in a corrosive environment greater than that of the interdendritic region. The chemical composition of this region and the interdendritic region is uneven, resulting in a large local potential difference, thereby accelerating the corrosion process. Therefore, the characteristic organization without DFZ area prepared by the present invention has greatly improved the recrystallization resistance, mechanical properties and corrosion properties of Al-Mg-Mn alloy. The present invention provides a new idea for preparing a high-performance Al-Mg-Mn alloy.
Claims
1. A method for promoting the precipitation and uniform distribution of a large amount of Mn-rich phase in an Al-Mg-Mn alloy, characterized in that: The specific steps include: Step 1: Obtain an aluminum alloy ingot by a conventional metal mold casting method, wherein the mass percentages of the constituent elements of the alloy are: Mg: 4.0-6.0wt.%, Mn: 0.4-1.0wt.%, Si: 0-0.4wt.% and not 0, Cr: 0-0.4wt.% and not 0, and the rest are Al and some inevitable impurities; Step 2: Cut off the head and tail of the ingot obtained in step 1, and take a sample from the center of the ingot for homogenization heat treatment; the homogenization heat treatment process is a three-stage homogenization, wherein the first stage heat treatment temperature is the precipitation temperature of the β' phase (usually 250°C-300°C), and the holding time is 8-12h; The sample after the first stage heat treatment is further heated up for the second stage heat treatment, wherein the second stage heat treatment temperature is the precipitation temperature of the Al-Mn second phase (usually 350°C-400°C), and the holding time is 12-60h; The sample after the second stage heat treatment is further heated up for the third stage heat treatment, wherein the third stage heat treatment temperature is the dissolution temperature of the primary β (Al3Mg2) phase in the Al-Mg alloy (usually 420°C-500°C), and the holding time is 8-24h; Step 3: Air cool the sample after the three-stage homogenization heat treatment to room temperature.
2. The method for promoting the precipitation and uniform distribution of a large amount of Mn-rich phase in an Al-Mg-Mn alloy according to claim 1, characterized in that: The heating rates of the first, second and third stages are all controlled to be no less than 0.5°C / min, but no more than 1.5°C / min, and the heating rates of the three stages are the same; preferably, the heating rate is controlled to be 1°C / min.
3. The method for promoting the precipitation and uniform distribution of a large amount of Mn-rich phase in an Al-Mg-Mn alloy according to claim 1, characterized in that: The mass percentages of the constituent elements of the alloy are: Mg: 4.0-6.0wt.%, Mn: 0.4-1.0wt.%, Si: 0-0.4wt.% and not 0, Cr: 0-0.4wt.% and not 0, and the rest are Al and some inevitable impurities.
4. The method for promoting the precipitation and uniform distribution of a large amount of Mn-rich phase in an Al-Mg-Mn alloy according to claim 1, characterized in that: The preferred addition amount of Si element (mass percentage) is: 0.1-0.2wt.%.
5. The method for promoting the precipitation and uniform distribution of a large amount of Mn-rich phase in an Al-Mg-Mn alloy according to claim 1, characterized in that: The preferred addition amount of Cr element (mass percentage) is: 0.1-0.2wt.%.
6. The method for promoting the precipitation and uniform distribution of a large amount of Mn-rich phase in an Al-Mg-Mn alloy according to claim 1, characterized in that: The first stage heat treatment temperature is 280℃ and the holding time is 12h.
7. The method for promoting the precipitation and uniform distribution of a large amount of Mn-rich phase in an Al-Mg-Mn alloy according to claim 1, characterized in that: The second stage heat treatment temperature is 375℃ and the holding time is 48h.
8. The method for promoting the precipitation and uniform distribution of a large amount of Mn-rich phase in an Al-Mg-Mn alloy according to claim 1, characterized in that: The third stage heat treatment temperature is 450℃ and the holding time is 12h.
9. An aluminum alloy obtained according to the method according to any one of claims 1 to 8.